Self-assembly of complex structures in colloid-polymer mixtures - Oğuz, Erdal; Mijailović, Aleksandar; Schmiedeberg, Michael (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2018)
If particles interact according to isotropic pair potentials that favor multiple length scales, in principle, a large variety of different complex structures can be achieved by self-assembly. Here, we study the specific example of colloid-polymer mixtures in which the effective interactions between colloids are dictated by a Aasakura-Osawa–type potential that possesses two length scales. Upon examining the phase behavior of two-dimensional colloid-polymer mixtures, we observe that nontrivial structures only occur in the vicinity of selected densities where triangular ordering is suppressed by the pair potential. Close to these densities, a large number of different phases self-assemble that correspond to tilings containing triangular, rhombic, square, hexagonal, and pentagonal tiles, and including some of the Archimedean tilings. We obtain the ground-state energies by minimizing the corresponding lattice sums with respect to particle positions in a unit cell as well as cell geometry and verify the occurrence of selected phases at finite temperatures by using Brownian dynamics simulations. We explain how the occurrence of nontrivial orderings can be predicted on a two-particle level by employing an enthalpylike pair potentials. Our work provides a manual on how to find the regions of nontrivial phases in parameter space for complex pair interactions in genera